2018
DOI: 10.3390/en11010149
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Thermal Performance of a Dry Storage Cask for Spent Nuclear Fuel

Abstract: Abstract:In this study, the heat flow characteristics and thermal performance of a dry storage cask were investigated via thermal flow experiments and a computational fluid dynamics (CFD) simulation. The results indicate that there are many inner circulations in the flow channel of the cask (the channel width is 10 cm). These circulations affect the channel airflow efficiency, which in turn affects the heat dissipation of the dry storage cask. The daily operating temperatures at the top concrete lid and the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These studies explained why the whole life cycle of nuclear energy needs to consume great amounts of fossil fuels. Furthermore, some scholars have debated the idea that nuclear energy decreases the consumption of fossil fuels, with studies indicating the radiation risks of nuclear energy [30][31][32]. Bowen et al [33] studied the price decline of the United States' energy stocks after the Three Mile Island incident.…”
Section: Introductionmentioning
confidence: 99%
“…These studies explained why the whole life cycle of nuclear energy needs to consume great amounts of fossil fuels. Furthermore, some scholars have debated the idea that nuclear energy decreases the consumption of fossil fuels, with studies indicating the radiation risks of nuclear energy [30][31][32]. Bowen et al [33] studied the price decline of the United States' energy stocks after the Three Mile Island incident.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding ventilated dry storage, there are more studies that have discussed heat removal [15][16][17][18]. Several studies have investigated thermal modeling of the natural convection using the ANSYS Fluent code.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modeling was also used in ventilated dry storage using computational fluid dynamics (CFD) to investigate several inner circulations in the cask at the flow channel. These circulations had an influence on the heat dissipation of the dry storage [15]. In another study, a comparison between numerical/mathematical modeling and experiments on temperatures at the inlet and outlet vents was conducted on ventilated dry storage in the Zaporizhska NPP [18].…”
Section: Introductionmentioning
confidence: 99%
“…CFD is also being used for heat transfer investigation of different nuclear waste processing technologies. Chang et al [25] investigated the heat flow characteristics and thermal performance of a dry storage cask both experimentally and by CFD simulations. They found that inner flow circulations occur in the flow channel of the cask, affecting the heat dissipation of the dry storage cask.…”
Section: Introductionmentioning
confidence: 99%